1993
DOI: 10.1007/bf02928026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of growth regulators onVicia faba plants irrigated by sea water Leaf area, pigment content and photosynthetic activity

Abstract: The antagonistic effects of some growth regulators [Le. indol-3-yl-acetic acid (IAA), gibberellic acid (GA3) or kinetin] on stress imposed by sea water on leaf area, pigment and photosynthetic activity in leaves of broad bean plants at different stages of development were investigated. Seed priming with GA 3 alleviated either partially or completely the effects induced by the two levels of sea water (10 and 25 %) used on leaf area at all experimental stages. However, IAA, GA 3 and kinetin inhibited leaf growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
15
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 18 publications
(9 reference statements)
9
15
0
Order By: Relevance
“…These results might explain the different effects of GA 3 and IAA on the WUE values obtained here. Furthermore, Aldesuquy and Gaber (1993) showed that, when seeds of Vicia faba were treated with IAA, GA 3 or kinetin and irrigated with seawater (10 and 25 %), these hormones either partially or completely alleviated the effects of salinity on leaf area at all growth stages. The same authors also found that IAA, GA 3 or kinetin counteracted the deleterious effects of seawater irrigation on photosynthetic activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results might explain the different effects of GA 3 and IAA on the WUE values obtained here. Furthermore, Aldesuquy and Gaber (1993) showed that, when seeds of Vicia faba were treated with IAA, GA 3 or kinetin and irrigated with seawater (10 and 25 %), these hormones either partially or completely alleviated the effects of salinity on leaf area at all growth stages. The same authors also found that IAA, GA 3 or kinetin counteracted the deleterious effects of seawater irrigation on photosynthetic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Gibberellic acid (GA 3 ) and indole-3-acetic acid (IAA) were found to increase the plant growth and pigment content of salinized plants (Younis et al 1991, Aldesuquy 1992, 2000. Aldesuquy and Gaber (1993) demonstrated in Vicia faba that seed treatment with IAA, GA 3 or kinetin alleviated either partially or completely the eects induced by two levels of seawater (10 % and 25 %) on leaf area, pigment content, Hill activity of isolated chloroplasts and leaf photosynthetic activity.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Aldesuquy and Gaber (1993) demonstrated in Vicia faba that seed treatment with IAA, GA 3 or kinetin alleviated either partially or completely the effects induced by irrigation with two levels of seawater (10 and 25 %) on leaf area, pigment content, Hill activity of isolated chloroplast and leaf photosynthetic activity.…”
Section: Introductionmentioning
confidence: 99%
“…These have been particularly implicated in apical dominance, chloroplast development, anthocyanin production, and regulation of cell division as well as source-sink relationships (Hutchison and Kieber 2002). Moreover, CYTs are regarded as the most important senescence-retarding hormones (Faiss et al 1997) and their exogenous application has been demonstrated to inhibit the degradation of Chl and photosynthetic proteins (Wingler et al 1998), besides elevating photosynthetic rate and levels of key photosynthetic enzymes (Synková et al 1997, Chernyad'ev and Monakhova 1998, Shah 2007, and substantially modifying plant responses to varied environmental stresses (Aldesuquy and Gaber 1992, El-Shibaby et al 2002, Shah 2011.…”
Section: --mentioning
confidence: 98%